An untold leadership story from land of hornbill / Kevin Anak Ong - Ong, Kevin Anak (2014)
First and foremost, I would like to convey my heartiest congratulation for TINTA committee for the December 2014 issue publishing. Good job well done to all of you for the hard work presented ever since. Please accept my gratitude for giving me the chance to write a long commentary, lifelong experience in my leadership ever since. As for me, nothing much to be presented, but a true life story of someone that was once born as an ordinary person. Here it goes to the next paragraph.